Estimating the Effects of Tunnelling on Preexisting Jointed Pipelines. (25th June 2019) - Yu, Shao; Duan, Zhibo; Liu, Ying; Ma, Min; Ma, Shaokun
Abstract : Tunnel excavation inevitably results in ground movements and changes in soil stress, leading to additional stress on and settlement of nearby buried pipelines. This article focuses on the response of jointed pipelines to twin tunnelling. The relationship between the relative pipe-soil displacement and the relative pipe-soil stiffness was first determined. Based on this analysis, a series of numerical parametric studies encompassing 7776 conditions were performed to investigate the responses of a jointed pipeline to twin tunnelling. The results are used to estimate a regression equation for the relationship between the relative pipe-soil stiffness and the normalized maximum joint rotation angle. This equation can be used for the direct calculation of the maximum joint rotation angle that will result from single or twin tunnelling and for the assessment of the tunnelling-induced risk to jointed pipelines. The applicability and reliability of the regression equation are validated by comparing the calculated values with the results of earlier centrifuge tests.